Net Benefits of the Integrated Academic Information System for the Academic Community of the Department of Electrical Engineering Education, Universitas Negeri Makassar: An Evaluation Using the DeLone & McLean Model - Hasrul Bakri (Fakultas Teknik Universitas Negeri Makassar, 2026)
Objectives: The JPTE Integrated Academic Information System (SIJUPE) was developed to address student data management problems at the Department of Electrical Engineering Education (JPTE), Faculty of Engineering, Universitas Negeri Makassar (FT UNM), which is one of the departments with the largest number of students. This study aims to evaluate the success of SIJUPE using the DeLone & McLean (2003) Information Systems Success Model, which encompasses three quality dimensions (system, information, service), use, user satisfaction, and net benefits. Methods: This research employed a quantitative approach with a survey method. The study population consisted of all SIJUPE users among the academic community, with samples taken using proportionate stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. Results: The results show that user satisfaction has a positive and significant effect on net benefits, as does system use. Among the three quality dimensions, information quality is the most dominant factor influencing user satisfaction. These findings indicate that SIJUPE generally provides positive benefits to the academic community of JPTE FT UNM, although improvements in service quality are still needed. Novelty: This study contributes first empirical evidence on the successful implementation of a cloud computing-based academic information system in a higher education setting with a large student population, specifically in Eastern Indonesia, using an integrated DeLone & McLean framework.